An Effect of Biocomposite Composition and Material on Brake Pad Wear - Yuniarto Agus Winoko; Achmad Dhani Audi Pratama; Umi Anis Ro'isatin (Department of Mechanical Engineering, Universitas Andalas, 2022)
Asbestos material which is widely used in brake pad friction material is carcinogenic is harmful to long term health. The method of making brake pads is by mixing the basic ingredients of brake linings from nature in the form of bamboo powder and bagasse ash with different percentages of mixtures of 25% bamboo powder, 35% bagasse ash and 40% polyurethane sample coded A. 35% bamboo powder , 25% bagasse ash and 40% polyurethane sample coded B. While 45% bamboo powder, 15% bagasse ash and 40% polyurethane sample coded C. Using compression molding with a compressive force of 14.709 N. The highest average hardness is 77, 4 HD was obtained on the brake lining coded A with the ratio of a mixture of 25% bamboo powder, 35% bagasse ash and 40% polyurethane. While the lowest average hardness value of 70.6 HD was obtained on brake pads with code C with a mixture ratio of 35% bamboo powder, 25% bagasse ash and 40% polyurethane.